The fabrication of the city between urban rule and urban project, case of Annaba city - Laouissi Naziha; Rehailia Hassib (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca, 2023)
The normative urban rule is a technical and hygienic rule which is essentially concerned with the rights to build on the land. Designed according to a purely quantitative vision, it constitutes a rigid regulation which imposes itself as a constraint devoid of meaning. Its dysfunctions and failures have led to its rejection and the emergence of a new trend: the urban project. This concept was nourished by the theoretical debates on historic centres in Italy around the 1960s. Following the example of Algerian cities, Annaba has witnessed the emergence of various emblematic projects in recent years. In order to know whether the approach followed is that of an urban project, a comparison of urban management between Annaba and three European cities has been made in this work. This study allows for the redefinition of the existing urban planning tools in order to put in place other innovative and more efficient ones.